Clostridium kogasensis sp. nov., a novel member of the genus Clostridium, isolated from soil under a corroded gas pipeline. (June 2016) - Shin, Yeseul; Kang, Seok-Seong; Paek, Jayoung; Jin, Tae Eun; Song, Hong Seok; Kim, Hongik; Park, Hee-Moon; Chang, Young-Hyo
Abstract: Two bacterial strains, YHK0403 T and YHK0508, isolated from soil under a corroded gas pipe line, were revealed as Gram-negative, obligately anaerobic, spore-forming and mesophilic bacteria. The cells were rod-shaped and motile by means of peritrichous flagella. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the isolates were members of the genus Clostridium and were the most closely related to C lostridium scatologenes KCTC 5588 T (95.8% sequence similarity), followed by C lostridium magnum KCTC 15177 T (95.8%), C lostridium drakei KCTC 5440 T (95.7%) and C lostridium tyrobutyricum KCTC 5387 T (94.9%). The G + C contents of the isolates were 29.6 mol%. Peptidoglycan in the cell wall was of the A1γ type with meso -diaminopimelic acid. The major polar lipid was diphosphatidylglycerol (DPG), and other minor lipids were revealed as phosphatidylglycerol (PG), phosphatidylethanolamine (PE), two unknown glycolipids (GL1 and GL2), an unknown aminoglycolipid (NGL), two unknown aminophospholipids (PN1 and PN2) and four unknown phospholipids (PL1 to PL4). Predominant fatty acids were C16:0 and C16:1 cis 9 DMA. The major end products from glucose fermentation were identified as butyrate (12.2 mmol) and acetate (9.8 mmol). Collectively, the results from a wide range of phenotypic tests, chemotaxonomic tests, and phylogenetic analysis indicated that the two isolates represent novel species of the genus Clostridium, for which the name Clostridium kogasensis sp. nov. (type strain, YHK0403 T  = KCTC 15258 T  = JCM 18719 T ) is proposed. Highlights: A novel Clostiridum species was isolated from soil under the corroded gas pipe line. A 16S rRNA gene sequence analysis demonstrated that the isolates belonged to the genus Clostridium. A novel species in the genus Clostridium, for which the name Clostridium kogasensis sp. nov. is proposed.